Focus on nocturia in the elderly. (August 2013) - Osman, Nadir I; Chapple, Christopher R
Nocturia is one of the most bothersome lower urinary tract symptoms and most common causes of disturbed sleep in the elderly. By fragmenting the sleep cycle, it leads to a negative impact on the quality of sleep and consequently is associated with daytime tiredness. Nocturia is also associated with falls and fall-related morbidity, as well as an incidence of mortality. Traditionally, nocturia has often been viewed as simply due to lower urinary tract dysfunctions, such as bladder outlet obstruction due to benign prostatic hyperplasia or overactive bladder syndrome, which has led to a failure to properly evaluate the condition in clinical practice and research. The contribution of nocturnal polyuria to the etiology of nocturia in elderly persons has led to new treatment approaches that focus on reducing night time urine production. This review discusses the current evidence on the etiology, epidemiology, pathogenesis and management of nocturia in the elderly.